2019
DOI: 10.1101/854851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functions of Gtf2i and Gtf2ird1 in the developing brain: transcription, DNA-binding, and long term behavioral consequences

Abstract: AbstractGtf2ird1 and Gtf2i may mediate aspects of the cognitive and behavioral phenotypes of Williams Syndrome (WS) – a microdeletion syndrome encompassing these transcription factors (TFs). Knockout mouse models of each TF show behavioral phenotypes. Here we identify their genomic binding sites in the developing brain, and test for additive effects of their mutation on transcription and behavior. Both TFs target constrained… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…S3A ), suggesting a more complex picture. Of note, SYN1 and NLGN1 are found among GTF2I targets (Kopp et al, 2020; McCleary-Wheeler et al, 2020). We next compared the iNeurons transcriptomes to a single-cell RNAseq time-course of Ngn2 differentiation (Lin et al, 2021), which revealed a slight differentiation delay of WBS lines ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…S3A ), suggesting a more complex picture. Of note, SYN1 and NLGN1 are found among GTF2I targets (Kopp et al, 2020; McCleary-Wheeler et al, 2020). We next compared the iNeurons transcriptomes to a single-cell RNAseq time-course of Ngn2 differentiation (Lin et al, 2021), which revealed a slight differentiation delay of WBS lines ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…USV recordings were performed as described in ref. 75 to assess early communicative behaviors. Pup vocalizations were recorded on postnatal days 5, 7, and 9 in the home colony room of the pups.…”
Section: Methodsmentioning
confidence: 99%
“…Pups were recorded for 3 min, after which their weight was taken and they were returned to their home cage within the warming box. MATLAB software was used to prepare sonograms of the recordings (frequency range = frequency range = 25-120 kHz, fast Fourier transform size = 512, overlap = 50%, time resolution = 1.024 ms, frequency resolution = 488.2 Hz) using a previously published protocol 75 .…”
Section: Methodsmentioning
confidence: 99%
“…Mouse models in which GTF2IRD1 specifically has been disrupted, in both a heterozygous and biallelic fashion, have variably recapitulated portions of the WBS neurocognitive profile, including increased anxiety, increased sociability, and impaired motor coordination depending on the model utilized (Howard et al, 2012; Schneider et al, 2012; Young et al, 2008). Most recently, Kopp et al generated mice with homozygous GTF2IRD1 variants, alone or in combination with disruption of GTF2I , and interestingly demonstrated that disruption of GTF2IRD1 alone was sufficient to generate significant behavioral anomalies in mice, with the addition of GTF2I disruption only marginally altering the phenotype (Kopp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%